2018
DOI: 10.5055/jom.2011.0045
|View full text |Cite
|
Sign up to set email alerts
|

Ziconotide: A rapid detoxification protocol for the conversion from intrathecal morphine–The Raffaeli Detoxification Model

Abstract: Objectives: To assess the efficacy and the safety of our rapid detoxification protocol in preventing signs and symptoms of withdrawal and pain severity.Design: Prospective, open-label case series study.Settings: Public primary care at the Pain and Palliative Care Unit of the Infermi Hospital of Rimini, Italy.Patients: The authors studied 10 consecutive patients suffering from chronic noncancer pain who were refractory to intrathecal (IT) morphine, and hence indicated for ziconotide therapy.Interventions: IT pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
4
3
0
Order By: Relevance
“…This suggests that ziconotide can be an advantage compared to classic IT therapies (morphine, local anaestics, and baclofen), since the majority of therapies used with patients (73%) before ziconotide administration had not determined a satisfactory pain reduction, or those therapies were interrupted for their related side effects (10%). The mean initial ziconotide dose was 1.41 µg/d, in agreement with studies suggesting low doses (45) and similar to those reported by Wallace et al (38). We observed the most common ziconotide-related side effects as previously reported in the literature: altered mood, confusion, memory deficit, abnormal CPK levels, vertigo, nausea (28,38,39,45).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This suggests that ziconotide can be an advantage compared to classic IT therapies (morphine, local anaestics, and baclofen), since the majority of therapies used with patients (73%) before ziconotide administration had not determined a satisfactory pain reduction, or those therapies were interrupted for their related side effects (10%). The mean initial ziconotide dose was 1.41 µg/d, in agreement with studies suggesting low doses (45) and similar to those reported by Wallace et al (38). We observed the most common ziconotide-related side effects as previously reported in the literature: altered mood, confusion, memory deficit, abnormal CPK levels, vertigo, nausea (28,38,39,45).…”
Section: Discussionsupporting
confidence: 90%
“…The mean initial ziconotide dose was 1.41 µg/d, in agreement with studies suggesting low doses (45) and similar to those reported by Wallace et al (38). We observed the most common ziconotide-related side effects as previously reported in the literature: altered mood, confusion, memory deficit, abnormal CPK levels, vertigo, nausea (28,38,39,45). They were mostly of mild or moderate intensity, however, no serious adverse events were observed and they did not always cause treatment interruption (18%).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations